Frequency of Intrauterine Death in Primigravida with Meconium Stained Liquor at Term - Fatima, Laraib; Khan, Ayesha; Naz, Tahira; Khan, Hina; Zafar, Ambreen; Khattak, Kashmal (Indus Journal of Bioscience Research, 2025)
Background: The intrauterine death remains a major obstetric complication, particularly in primigravida who present with amniotic fluid containing meconium. Identification of concomitant attendant demographic risk factors facilitates selective surveillance as well as early intervention, especially in low-resource hospital settings. Objective: To determine the frequency of intrauterine death in primigravida with meconium stained liquor at term. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from November 2022 to May 2023 at the Department of Obstetrics and Gynaecology, Hayatabad Medical Complex, Peshawar. Methodology: A total of 126 primigravida women aged 18–40 years with singleton pregnancies beyond 36 weeks gestation and meconium-stained liquor on ultrasound were enrolled. Patients with abnormal fetal presentation, congenital anomalies, or maternal comorbidities were excluded. Data were collected prospectively, and fetal outcomes were monitored until delivery. Results: The mean maternal age was 29.83 ± 4.64 years and mean gestational age was 39.37 ± 1.68 weeks. The frequency of intrauterine death was 4.80%. A significant association was found with maternal age (p=0.007) and socioeconomic status (p=0.012), while gestational age showed no significant relationship (p=0.418). Multivariate analysis identified maternal age >30 years as a significant predictor of intrauterine death (OR=0.21, p=0.017). Conclusion: In primigravida women with meconium-stained liquor, maternal age over 30 years significantly increases the risk of intrauterine death.